A study on the impact of patient-related parameters in the ability to spare parotid glands by intensity-modulated radiotherapy for head and neck squamous cell carcinomas - Bandlamudi, Bhanu; Sharan, Krishna; Yathiraj, Prahlad; Singh, Anshul; Reddy, Anusha; Fernandes, Donald; Srinivasa, Vidyasagar (Journal of cancer research and therapeutics, 2018)
Aims and Objectives: This study aims to study the effect of geometric- and patient-related variables in achieving the desired dose-volume constraints to parotid for patients undergoing definitive/adjuvant intensity-modulated radiotherapy (IMRT) for head and neck squamous cell carcinomas (HNSCC). Subjects and Methods: This retrospective study considered HNSCC patients who underwent IMRT at our center between 2009 and 2014. Patients' details and dose-volume parameters were collected, and correlated with dose to parotids using Pearson's correlation test. Results: Sixty-seven patients were found to be eligible. Oral primary predominated (37.3%) and 53 (79%) had locally advanced disease. The parotid volume (PV) had no impact on mean dose. There was a negative linear correlation between the ratio (Parotid-planning target volume [PTV] overlap)/PV and mean dose to the whole parotid (y = 1.14-0.011×; R2 = 0.509; P = 0.001), suggesting that a ratio of 0.7 resulted in mean dose ≥ 40 Gy and potentially irreversible xerostomia. No association was found between site of primary and parotid dose, but node-positive (N+) patients received significantly higher dose compared to N0 patients (34.5 Gy vs. 29.5 Gy; P = 0.001). N + patients persisted to receive higher dose even when T stage was accounted for (32.5 Gy vs. 28.9 Gy for </= T2, 35.4 Gy vs. 30.1 Gy for > T2; P = 0.003). On the last follow-up, 35 patients (52%) had >/=Grade II xerostomia. Average mean dose to combined PV was higher in patients with > grade I xerostomia compared to patients with </=Grade I (35 Gy vs. 29 Gy; P = 0.01). Conclusion: The degree of PTV overlap with parotid (≥30%) and N + disease are the strongest predictors of poor parotid sparing by IMRT.